Axonal transport deficits in the pathogenesis of diabetic peripheral neuropathy - Yang, Cunqing; Zhao, Xuefei; An, Xuedong; Zhang, Yuehong; Sun, Wenjie; Zhang, Yuqing; Duan, Yingying; Kang, Xiaomin; Sun, Yuting; Jiang, Linlin; Lian, Fengmei (Frontiers in Endocrinology, 2023)
Diabetic peripheral neuropathy (DPN) is a chronic and prevalent metabolic disease that gravely endangers human health and seriously affects the quality of life of hyperglycemic patients. More seriously, it can lead to amputation and neuropathic pain, imposing a severe financial burden on patients and the healthcare system. Even with strict glycemic control or pancreas transplantation, peripheral nerve damage is difficult to reverse. Most current treatment options for DPN can only treat the symptoms but not the underlying mechanism. Patients with long-term diabetes mellitus (DM) develop axonal transport dysfunction, which could be an important factor in causing or exacerbating DPN. This review explores the underlying mechanisms that may be related to axonal transport impairment and cytoskeletal changes caused by DM, and the relevance of the latter with the occurrence and progression of DPN, including nerve fiber loss, diminished nerve conduction velocity, and impaired nerve regeneration, and also predicts possible therapeutic strategies. Understanding the mechanisms of diabetic neuronal injury is essential to prevent the deterioration of DPN and to develop new therapeutic strategies. Timely and effective improvement of axonal transport impairment is particularly critical for the treatment of peripheral neuropathies.